'SI‐SRH' – a new model to manage sexual health following a spinal cord injury: our experience. Issue 23 (December 2013) - Hartshorn, Carly; D'Castro, Emma; Adams, Jillian
Abstract : Aims and objectives: To maximise involvement of the multidisciplinary team using a model of sexual health management for spinal cord‐injured persons. Background: Regaining sexual function is a priority following spinal cord injury, with the majority of people remaining sexually active with a satisfying sex life. Nevertheless, rehabilitation programmes often focus on activities related to mobility and elimination, with sexual health relegated to a secondary under‐resourced position. Design: Model creation and audit of current and desired status to identify required education. Methods: A four‐tier model for sexual health management identified phases of management, increasing in complexity, from tier 1 to tier 4. The model was used to audit the current and desired status of the multidisciplinary team on a spinal injuries unit, identifying knowledge levels, barriers to involvement and education requirements. Results: Fifty‐nine questionnaires were completed (85%) by nurses and allied health professionals. Knowledge deficits and discomfort with the topic were the primary reasons prohibiting involvement with sexual health rehabilitation. Two thirds were willing to be involved with sexual health activities, mainly at an introductory level rather than providing education or problem‐solving. However, following relevant education, the level of involvement changed: 90% ( n = 53) desired involvement at more complex levels, and 10% ( n = 6) were unwilling to be involved. Conclusions: Developing the necessary skills and knowledge creates potential to increase the resources available to participate in sexual health rehabilitation following a spinal cord injury and ensure that it is a core rehabilitation activity. Relevance to clinical practice: The progressive model portrayed discrete phases of sexual health management, which collectively portray the whole. Team members identified a level of involvement to compliment their skills and knowledge. The audit demonstrated that the primary barriers to involvement were not culture, language or attitude as hypothesised, but inadequate knowledge, addressable through education.